The exceptional advantages of channeling implantation into 4H-SiC to make abrupt deep profiles. (1st May 2022) - Wada, Ryota; Nagayama, Tsutomu; Tokoro, Nobuhiro; Kuroi, Takashi; Das, Hrishikesh; Sunkari, Swapna; Justice, Joshua
Abstract: We investigated the channeling implantation of dopant ions into 4H-SiC in detail. The advantages of channeling implantation were clarified by both experimental and Monte Carlo simulation. Extremely abrupt deep profile with box-like can be formed by channeling implantation of Al and P ions. In the case of B and N ions, retrograde-like profile can be obtained by channeling implantation. The unique dopant profile can be realized by channeling implantation. Both vertical and lateral straggling becomes small by using channeling implantation for Al ions. This technique should contribute to improving the device performance such as gate pitch scaling and low specific on-resistance.